2016
DOI: 10.1007/s13679-016-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Pediatric Obesity in Ambulatory Care: Where Are We and Where Are We Going?

Abstract: Since the “2007 summary report of child and adolescent overweight and obesity treatment” published by Barlow, many obesity intervention studies have been conducted in pediatric ambulatory care. Although several meta-analyses have been published in the interim, many studies were excluded because of the focus and criteria of these meta-analyses. Therefore, the primary goal of this article was to identify randomized case-control trials conducted in the primary care setting and to report on treatment approaches, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…However, in this pilot study we sought to conduct an intervention in a real-world primary care setting that would likely have limited resources in terms of incentives for patients participating, as well as limited professional staff available to support a treatment intervention. Previous research has documented similar findings of low enrollment and high attrition in real-world childhood obesity treatment settings and identified a great need for additional research in these settings [22][23][24][25].…”
Section: Discussionmentioning
confidence: 71%
“…However, in this pilot study we sought to conduct an intervention in a real-world primary care setting that would likely have limited resources in terms of incentives for patients participating, as well as limited professional staff available to support a treatment intervention. Previous research has documented similar findings of low enrollment and high attrition in real-world childhood obesity treatment settings and identified a great need for additional research in these settings [22][23][24][25].…”
Section: Discussionmentioning
confidence: 71%
“…In our study, 33.9% of children dropped out, which is slightly lower than the median of 37% found in a review on paediatric obesity management by Dhaliwal et al 23 This is noteworthy because children in deprived areas, as compared with nondeprived areas, are usually less likely to complete a weight-loss intervention programme. 5 , 7 , 11 However, there is still substantial room for improvement. Previous research showed that children who have parents who are more involved, adhere better to the intervention and lose significantly more weight.…”
Section: Discussionmentioning
confidence: 99%
“… 2 The limited effectiveness of these intervention programmes is often thought to be the result of low compliance 3–6 and high dropout rates. 7 …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that medical students feel unfamiliar with obesity prevention and treatment. Self-reporting by pediatricians and primary care physicians demonstrated they also feel unprepared to successfully provide care to children with obesity (9)(10)(11).…”
Section: Study Importancementioning
confidence: 99%